STUDI PEMANFAATAN LISTRIK UNTUK MENAIKAN TAHANAN PENTANAHAN KAKI MANUSIA PADA AREA GARDU INDUK PT SEMEN PADANG - Rosnita Rauf (Situs resmi ITP Press, 2014)
One of the most important aspects to design a secure grounding system is the resistance of the foot, where the prisoner's feet need to have high resistivity. Because prisoners foot greatly influences the magnitude of touch voltages in the substation, then the detainee raise big toe will automatically affect the voltage. To get custody feet high polyethelene plastic used as insulating soil that produces 90.71% increase soil prisoners, so expect to plan a substation that has good soil prisoners and detainees are also sizable land them using polyethelene plastic, with plastic thickness and different weather.